Analisis Tingkat Kepuasan Penumpang Kereta Cepat terhadap Fasilitas dan Pelayanan Stasiun Halim Menggunakan SERVQUAL Berbasis Website - Deby Ika Hariani; Renna Melinda; Wida Yuliar Rezika; Daryono Daryono; Arnelita Khusnul Wardani (Jurnal Talenta Sipil, 2026)
The rapid development of high-speed railways requires service providers to continuously improve station facilities and service quality to meet passenger expectations. Although the Service Quality (SERVQUAL) method has been widely applied to evaluate service quality, studies integrating data collection, processing, and real-time visualisation into a single web-based platform remain limited, particularly in Indonesia's high-speed railway services. This study aims to analyse passenger satisfaction with the facilities and services at Halim Station using a web-based SERVQUAL approach while developing a digital platform to support continuous service evaluation. A quantitative approach was employed involving 131 respondents selected through purposive sampling. Data were collected using a web-based questionnaire measuring passengers' perceptions and expectations and were analysed through validity and reliability tests, followed by SERVQUAL gap analysis across five service quality dimensions. The results indicate that all questionnaire items are valid and reliable, and the overall service quality of Halim Station is classified as very good, with an average perception score of 4.5974. Positive gaps were identified in the responsiveness, assurance, and empathy dimensions, whereas the tangibles and reliability dimensions exhibited slight negative gaps, indicating areas requiring improvement. This study develops a web-based system that integrates questionnaire data collection, SERVQUAL gap calculation, data recapitulation, and survey result visualisation. The system helps improve the efficiency of service monitoring and assists in making decisions based on station management data. By combining SERVQUAL with a digital web-based platform, this approach offers a more efficient method for supporting continuous service quality evaluation in railway station services.